Cohesive Devices in Advertising Discourse - SAOUCHA, Amel (Journal of Human Sciences, 2014)
The present study aims at investigating the cohesive devices used in advertising discourse, more precisely, in audiovisual advertising discourse.In order to examine how cohesion is achieved, ten television commercials in English are selected as the main source of data,and are analyzed within the framework of Halliday and Hasan’smodel of cohesion.The findings of the study suggest that cohesion is caused by the high number of reiteration instances as well as collocation pairs. The study concludes that lexical cohesive devices are dominant in advertising discourse. Conversely, grammatical cohesive devices are less frequent in the advertisements under study.